Pannexin 3 regulates skin development via Epiprofin - Zhang, Peipei (Sci Rep, 2021)
Pannexin 3 (Panx3), a member of the gap junction pannexin family is required for the development of hard tissues including bone, cartilage and teeth. However, the role of Panx3 in skin development remains unclear. Here, we demonstrate that Panx3 regulates skin development by modulating the transcription factor, Epiprofin (Epfn). Panx3(−/−) mice have impaired skin development and delayed hair follicle regeneration. Loss of Panx3 in knockout mice and suppression by shRNA both elicited a reduction of Epfn expression in the epidermis. In cell culture, Panx3 overexpression promoted HaCaT cell differentiation, cell cycle exit and enhanced Epfn expression. Epfn(−/−) mice and inhibition of Epfn by siRNA showed no obvious differences of Panx3 expression. Furthermore, Panx3 promotes Akt/NFAT signaling pathway in keratinocyte differentiation by both Panx3 ATP releasing channel and ER Ca(2+) channel functions. Our results reveal that Panx3 has a key role factor for the skin development by regulating Epfn.